Finite Element Prediction of Heat-Affected Zone in Laser-micromachining of Silicon - T. T., Mon; M. M., Noor; R. A., Bakar; M. R. M., Rejab (2008)

(untitled)
Silicon has been a major material used for fabricating MEMS devices that are now potentially a far more pervasive technology. In processing of silicon material, laser-micromachining has been increasingly employed. However, laser debris and thermal crack are problematic with laser machining and also sensitive issues with MEMS devices. This paper highlights finite element simulation of laser-micromachining of silicon as a start point of research in investigating material response to thermal effect. Simulation uses standard commercial software. Finite element model was developed with the plate and thermal rod elements using 2D mesh generator. Currently, the isotropic properties of silicon were assumed and material properties were taken from published reports. The database translation utility was modified to specify a time-dependent nodal heat flux for laser source. Thermal transient heat transfer analysis was chosen for simulation of laser-micromachining. The temperature distributions in silicon material during laser-micromachining of different geometries as well as with different pulse energies are presented and discussed. Heat-affected zone is well-identified.